A Disciplined Dissident—Aung San Suu Kyi as Opposition Backbencher (2012–2016). Issue 1 (4th June 2021) - Egreteau, Renaud
Abstract: This article investigates the legislative activity of Aung San Suu Kyi, Myanmar's iconic dissident, during her inaugural tenure as opposition MP in the country's first post-junta parliament (2012–2016). How did such a totemic figure behave in a legislature dominated by an army-backed party and military-appointed MPs? What legislative tools did she use? The study draws evidence from Burmese-language proceedings of Myanmar's Union legislature and field interviews. The findings point to a largely marginal, yet disciplined, involvement of Aung San Suu Kyi in legislative business. She neither acted as party whip nor openly criticised government record or took disruptive action in the context of Myanmar's 'discipline-flourishing democracy'. Yet, she joined policy debates through the occasional motion, used her position as a catalyst for engaging the government and the world, and successfully marshalled her party to win the next two general elections in 2015 and 2020. The findings have implications for understanding how the strategies of such near-mythical figure can explain subsequent electoral or political (mis)fortunes.